MENGUBAH SAMPAH MENJADI ESTETIKA: PEMBERDAYAAN MASYARAKAT MELALUI KERAJINAN BUNGA KAMBOJA DARI PLASTIK KRESEK - Yofina Amurdi; Angelina M. L. D. Onjur; Maria E. N. Harni; Priska P. Naut; Odilia H. Amung; Dionisia E. P. Hadu; Hironimus Kabul (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Plastic waste has become an environmental issue that requires solutions based on active community participation. This community service program was conducted to empower local residents to transform plastic bag waste into frangipani (plumeria) flower handicrafts with aesthetic and functional value. The activity employed a qualitative descriptive approach and was carried out through training and mentoring sessions involving women in Ngencung Village, Langke Rembong District, Manggarai Regency, East Nusa Tenggara, Indonesia. The program was implemented through hands-on practice, allowing participants to directly produce frangipani flowers from plastic bags. Data were collected through observation and documentation and were analyzed descriptively. The results show that participants demonstrate improved skills and creativity in processing plastic waste into handicrafts. The activity also increases community awareness of the importance of proper plastic waste management. In conclusion, this program contributes to reducing plastic waste and shows potential to be further developed as an environmentally based community economic empowerment initiative.